The minimum marriageable age policy process in the United States: An advocacy coalition framework analysis. - Ikpebe, Ene (Review of Policy Research, 2026)
Early marriage—defined as marriage before age 18—has been shown to constitute a major obstacle to women's development with negative impacts on their health, education, and economic development. For several decades, the issue has been a major topic of global policy discussions with organizations like the United Nations advocating for global adoption of a minimum marriageable age of 18. However, for almost all this period, American policy discussions have not reflected a similar prioritization of the issue of early marriage; Delaware was the first state to adopt the policy in 2018. Using the Advocacy Coalition Framework (ACF), this paper examines the development of the minimum marriageable age policy discussion in the United States. With Discourse Network Analysis (DNA) of newspaper articles, the study identifies the major actors, coalitions, and beliefs that have featured in this policy process. The analysis suggests that NGOs and state legislators have been the main policy actors, and that they can be organized into pro and anti‐minimum‐marriageable‐age‐of‐18 coalitions. Results also show that the deep core beliefs that have featured in the policy discussion boil down to the American ideal of liberty, in this case, of individuals to marry, to exercise their reproductive and religious rights, of parents to decide when their children are ready for marriage, and to not suffer violation of other human rights.